Liability for Negligent Misrepresentation in the Finance Industry - Sadler, Pauline (School of Business Law, Curtin Business School, Curtin University of Technology, 2009)
Sometimes statements made by people working in the finance industry when giving advice may be incorrect. This article examines how the tort of negligence applies to the making of these misrepresentations. Cases discussed include Hedley Byrne & Co Ltd v Heller & Partners Ltd [1964] AC 465, Mutual Life & Citizens Assurance Co Ltd v Evatt (1968) 122 CLR 556, Shaddock & Associates Pty Ltd v Parramatta City Council (1980-1981) 150 CLR 225, Tepko Pty Ltd v Water Board (2001) 206 CLR 1, Caparo Industries plc v Dickman [1990] 2 AC 605 and Esanda Finance Corporation Ltd v Peat Marwick Hungerfords (1997) 188 CLR 241.